Pengaturan Pembungaan Tanaman Manggis (Garcinia mangostana L.) di Luar Musim dengan Strangulasi, serta Aplikasi Paklobutrazol dan Etepon - I Nyoman Rai; Roedy Poerwanto; Latifah K. Darusman; Bambang S. Purwoko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2004)
The objective of the research was to study the application of strangulation, packlobutrazol and ethephon to stimulate flowering of mangosteen trees. The experiment was conducted from June 2002 to September2 003, located at Farmer's Mangosteen Orchards, Leuwiliang, Bogor. A randomized block design with two factors was used in thisexperiment. The first factor was treatments to stimulate flowering consisted of three levels i.e strangulation (8), (S) application of paclobubtrazol (P) and control (K). The second factor was treatments for dormancy breaking consisted of two levels i.e without ethephon (Eo) and with ethephon (EiJ. Each treatment was replicated four times. The resultshowed that strangulation and application of paclobutrazol were effective in stimulating flowering of mangosteen trees. Those treatments decreased gibberellic acid content and increased total sugar and C: N ratio. Interaction effect was found between treatments to stimulate flowering and ethephon on number of flowers, number of fruits and weight of fruits per tree. The highest fruits weight (2.,50 kg/tree) was obtained on the combination of paclobutrazol with ethephon while the lowest was in control without ethephon( 6.05 kg/tree).Key words: Mangosteen, Strangulation, Paclobutrazol, Ethephon, Flowering;